Comparative predictive value of APACHE-II, SAPS-II and GRACE scores for mortality in acute coronary syndrome (ACS) patients: Evidence from Indonesia intensive cardiovascular care unit registry - Prasetya, Indra; Hakim, Dennis I.; Anjarwani, Setyasih; Bagaswoto, Hendry P.; Muzakkir, Akhtar F.; Habib, Faisal; Astiawati, Tri; Wirawan, Hendy; Ilhami, Yose R.; Djafar, Dewi U.; Sungkar, Safir; Danny, Siska S.; Juzar, Dafsah A. (Narra J, 2025)
The Global Registry of Acute Coronary Events (GRACE) score is acknowledged for its ability to predict in-hospital mortality among patients with acute coronary syndrome (ACS). However, intensive care physicians often employ general prognostic scores such as Acute Physiologic and Chronic Health Evaluation II (APACHE-II) and Simplified Acute Physiology Score II (SAPS-II) to predict the mortality of ACS patients. However, their predictive values are not well-determined in predicting mortality in ACS treated in the cardiovascular care unit (CVCU). The aim of this study was to evaluate the performance of APACHE-II and SAPS-II scores in comparison with GRACE scores in predicting the CVCU mortality and in-hospital mortality of ACS patients admitted to CVCU. A multicenter retrospective cohort study was conducted using data from a registry of patients admitted to 10 hospitals in Indonesia between August 2021 and July 2023. This study evaluated the APACHE-II, SAPS-II, and GRACE scores for patients with ACS upon admission to CVCU. The area under the curve (AUC) of the receiver operating characteristic (ROC) was utilized to assess the discriminative ability for predicting mortality. Among the 12,950 admitted patients, 9,040 were diagnosed with ACS, and 6,490 patients were included in the final analysis. All three scoring systems had relatively good discriminative ability to predict CVCU mortality with APACHE-II having better results (AUC: 0.771; sensitivity: 63.9%; specificity: 78.7%) compared to GRACE (AUC: 0.726; sensitivity: 61.7%; specificity: 73.2%) and SAPS-II (AUC: 0.655; sensitivity: 38.9%; specificity: 85.2%). To predict in-hospital mortality, APACHE-II had better results (AUC: 0.815; sensitivity: 68.7%; specificity: 80.4%) compared to GRACE (AUC: 0.769; sensitivity: 64.6%; specificity: 77.5%) and SAPS-II (AUC: 0.683; sensitivity: 41.8%; specificity: 86.2%). APACHE-II had the best single risk factor for CVCU mortality (odds ratio (OR): 1.198; 95% confidence interval (CI): 1.181–1.214) and in-hospital mortality (OR: 1.259; 95%CI: 1.240–1.279). In conclusion, APACHE-II, SAPS-II, and GRACE scores moderately predict CVCU and in-hospital mortalities, with the APACHE-II score exhibiting the highest predictive capability in ACS patients admitted to CVCU.